Legal consciousness and Hong Kong cinema. Issue 1 (2nd January 2016) - Wan, Marco
Abstract : This article seeks to elucidate the role cinematic images of law play in the consolidation and transformation of a society's legal consciousness, or the ways in which its inhabitants perceive the legal system, through a discussion of three iconic Hong Kong films about the legal process. The films are chosen from the period between 1984 (the year an international treaty on the return of Hong Kong from Britain to China was signed) to 1997 (the year of the retrocession). It builds on existing work in 'law and film', and situates the films in the context of the legal changes that emerged as the city entered the final years of British colonial rule.